PENGARUH BRAND IMAGE, TATA LETAK DAN DISKON TERHADAP IMPULSE BUYING DI MATAHARI DEPARTMENT STORE MALL BALI GALERIA - Ni Made Sri Udayani; Ni Putu Nita Anggraini; Pande Ketut Ribek (VALUES, 2022)
This research aims to find out and analyze the influence of Brand Image, layout and discounts on Impulse buying at Matahari Department Store Mall Bali Galeria. The population in this study was all visitors to Matahari Departement Store Mall Bali Galeria who coincidentally met with researchers. Sampling in this study using nonprobability sampling methods, obtained by 97 respondents. The analysis method used is Multiple Linear Regression Analysis with data collection using questionnaires and processed with SPSS version 25. The results showed that Brand Image, Layout and Discounts had a positive effect on Impulse buying. Brand image is the most dominant variable in influencing impulse buying.